ADVANTAGES AND IMPORTANCE OF NATURAL DYES IN THE RESTORATION OF TEXTILE CULTURAL HERITAGE - (:unkn) unknown (UNIV ALEXANDRU IOAN CUZA IASI, ARHEOINVEST INTERDISCIPLINARY PLATFORM, 2016)
Identification of an art object material of cultural heritage had received significant attention, because of its importance for the development of appropriate restoration and conservation strategies. In this paper, optical microscopy, CIE L*a*b* spectrophotometer/colorimeter, scanning electron microscopy (SEM) coupled to energy dispersive X-ray (EDX) spectroscopy and high performance liquid chromatography coupled to diode-array-detection (HPLC-DAD) are used to investigate many historical textiles samples in some museums.
Keywords: Natural dyes; Restoration; Cultural heritage; HPLC-DAD; SEM-EDX; Colour measurements; HPLC-DAD; IDENTIFICATION; COTTON; SILK; DYESTUFFS; FASTNESS; COLOR; REUSE; L.